2007
DOI: 10.1073/pnas.0703702104
|View full text |Cite
|
Sign up to set email alerts
|

Solution mapping of T cell receptor docking footprints on peptide-MHC

Abstract: T cell receptor (TCR) recognition of peptide-MHC (pMHC) is central to the cellular immune response. A large database of TCR-pMHC structures is needed to reveal general structural principles, such as whether the repertoire of TCR/MHC docking modes is dictated by a ''recognition code'' between conserved elements of the TCR and MHC genes. Although Ϸ17 cocrystal structures of unique TCRpMHC complexes have been determined, cocrystallization of soluble TCR and pMHC remains a major technical obstacle in the field. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 29 publications
4
46
0
Order By: Relevance
“…However, recent studies clearly demonstrated that additional factors, such as Ag dose, peptide-MHC potency, as well as T cell and DC frequencies, essentially contribute to the stability of early T cell-DC interactions (31)(32)(33)(34). It is therefore not surprising that studies addressing T cell-DC interactions under tolerizing conditions have reported different kinetics of DC-T cell interaction: Hugues et al (11) found a three-phase kinetic of T cell-DC interactions, whereas Zinselmeyer et al (13) describe the existence of an early phase, when T cells form transient contacts at 8 h after Ag delivery, and a late phase characterized by stable contact formation ∼20 h after Ag delivery.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies clearly demonstrated that additional factors, such as Ag dose, peptide-MHC potency, as well as T cell and DC frequencies, essentially contribute to the stability of early T cell-DC interactions (31)(32)(33)(34). It is therefore not surprising that studies addressing T cell-DC interactions under tolerizing conditions have reported different kinetics of DC-T cell interaction: Hugues et al (11) found a three-phase kinetic of T cell-DC interactions, whereas Zinselmeyer et al (13) describe the existence of an early phase, when T cells form transient contacts at 8 h after Ag delivery, and a late phase characterized by stable contact formation ∼20 h after Ag delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Some information could be obtained on MHCII complexes by detecting the bound peptide (17,18). NMR analysis of the MHC protein itself was only possible for the MHCI-β 2 -microglobulin (19-21), a murine single-chain construct of an MHCI heavy chain fragment (22), and a fragment of a murine class II MHC (23). In this study we use backbone NMR assignment of an MHCII subunit to investigate the dynamic reorientation of CLIP variants in complex with HLA-DR1.…”
Section: Discussionmentioning
confidence: 99%
“…Protein was purified by gel filtration and ion exchange chromatography on mono-Q, showing a single, monodisperse peak in the chromatogram. Isotope-labeled preparations of H2-L d were made with a similar protocol but instead using 13 C-, 15 N-, and 2 H-substituted M9 minimal media to prepare the inclusion bodies as described for m04 (11).…”
Section: Methodsmentioning
confidence: 99%
“…Toward this end, we prepared samples of the mini-H2-L d construct refolded in vitro with two different peptides. In particular, we used the QL9 peptide (21) (also employed previously to study binding to the 2C TCR (13,16,17)) and a high affinity NIH self-peptide. Although initially, both samples gave well dispersed two-dimensional TROSY spectra, each indicative of a properly conformed peptide⅐ MHC-I complex, the sample prepared with QL9 deteriorated within 1 week at 25°C.…”
Section: Direct Interaction Between M06 and H2-l D Mhc-i-initialmentioning
confidence: 99%
See 1 more Smart Citation